2012
DOI: 10.1002/chem.201201499
|View full text |Cite
|
Sign up to set email alerts
|

Acceptor‐Substituted Ferrocenium Salts as Strong, Single‐Electron Oxidants: Synthesis, Electrochemistry, Theoretical Investigations, and Initial Synthetic Application

Abstract: A series of mono- and 1,1'-diheteroatom-substituted ferrocene derivatives as well as acylated ferrocenes was prepared efficiently by a unified strategy that consists of selective mono- and 1,1'-dilithiation reactions and subsequent coupling with carbon, phosphorus, sulfur and halogen electrophiles. Chemical oxidation of the ferrocene derivatives by benzoquinone, 2,3-dichloro-5,6-dicyanobenzoquinone, AgPF(6), or 2,2,6,6-tetramethyl-1-oxopiperidinium hexafluorophosphate provided the corresponding ferrocenium sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
67
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 76 publications
3
67
0
Order By: Relevance
“…PClnBu 2 , [77] PClnBu(NEt 2 ), [78] BrFc, [79] cis-[PtCl 2 (SEt 2 ) 2 ], [80] trans-[Pt(CϵCFc) 2 -(PnBu 3 ) 2 ], [47] [PtCl 2 (PnBu 3 ) 2 ], [48] and [Cu(CϵCFc)] [81] were prepared according to published procedures.…”
Section: Methodsmentioning
confidence: 99%
“…PClnBu 2 , [77] PClnBu(NEt 2 ), [78] BrFc, [79] cis-[PtCl 2 (SEt 2 ) 2 ], [80] trans-[Pt(CϵCFc) 2 -(PnBu 3 ) 2 ], [47] [PtCl 2 (PnBu 3 ) 2 ], [48] and [Cu(CϵCFc)] [81] were prepared according to published procedures.…”
Section: Methodsmentioning
confidence: 99%
“…When FcH had been removed (composition monitored by 1 H NMR spectroscopy between washings), the organic phase was extracted with water until the washings were colorless, dried over MgSO 4 and filtered (50 g silica/n-hexane). 52 A mixture of ferrocene (0.911 g, 4.90 mmol, 1 eq. ), potassium tert-butoxide (0.067 g, 0.60 mmol, 0.12 eq.)…”
Section: Experimental General Considerationsmentioning
confidence: 99%
“…11 Very thorough investigation of the oxidation of ferrocene derivatives by benzoquinone, 2,3-dichloro-5,6-dicyano-1,4-benzoquinone, and 2,2,6,6-tetramethylpiperidin-1-oxyl (TEMPO) was performed by Jahn and co-workers. 12 They found that 2,3-dichloro-5,6-dicyano-1,4-benzoquinone is preferred for the oxidation of ferrocene derivatives with strong electron-attracting groups, like Bz, CO 2 i-Pr, POPh 2 , etc. The prepared ferrocenium cations were isolated as the hexafluorophosphate salts and they were stable in acetonitrile or dichloromethane, but slowly reduced to the starting ferrocene derivatives in ethereal solvents, N,N-dimethylformamide, or dimethyl sulfoxide.…”
Section: Methodsmentioning
confidence: 99%
“…Catalysis by the ferrocenium ion led to much better results (57% yield) than with Brønsted acid (TsOH) catalyzed reactions. Even more importantly, the reaction was more selective, proceeding without the formation of undesired larger (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) calixarenes (Scheme 8).…”
Section: Methodsmentioning
confidence: 99%